If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6f=-66
We move all terms to the left:
6f-(-66)=0
We add all the numbers together, and all the variables
6f+66=0
We move all terms containing f to the left, all other terms to the right
6f=-66
f=-66/6
f=-11
| 5(x+5)=5x-1 | | 5n+-4n=5 | | -12+2x=-14 | | 5-x-x=- | | 3v-42=5(v-6) | | 2n-13=-19(16+4n) | | a/9=1/23 | | 289=69-u | | 2(x-2)=5x-16 | | -30=12-6x | | 5/8=3/y | | 6x+12+7x=-4 | | -2(x^2-7)^2+3=-47 | | 4(k+9)=4(k+9) | | −4−0.2x+11=−0.8x+10 | | 5x−7=58 | | −4−0.2x+11=−0.8x+10 | | 5x−2=3x+1 | | 12=0.005x | | 116(x−40)=5+x | | 11-3a+6=27 | | 5(x−2)=3x+1 | | 6(x+6)=6x+4 | | −5(3x−15)=2(x−1)−59 | | 10h+4=11 | | 7b^2+3b+42=0 | | 3x-6+4x=18-x | | 3(x-8)=7x-20 | | -x/5=22 | | 1/d+6=10 | | 6+x+9=6+x+9 | | 9x=7(×+1.75) |